Genotype-Phenotype Characterization of Novel Variants in Six Italian Patients with Familial Exudative Vitreoretinopathy. (5th July 2017) - Iarossi, Giancarlo; Bertelli, Matteo; Maltese, Paolo Enrico; Gusson, Elena; Marchini, Giorgio; Bruson, Alice; Benedetti, Sabrina; Volpetti, Sabrina; Catena, Gino; Buzzonetti, Luca; Ziccardi, Lucia
Abstract : Familial exudative vitreoretinopathy (FEVR) is a complex disorder characterized by incomplete development of the retinal vasculature. Here, we report the results obtained on the spectrum of genetic variations and correlated phenotypes found in a cohort of Italian FEVR patients. Eight probands (age range 7–19 years) were assessed by genetic analysis and comprehensive age-appropriate ophthalmic examination. Genetic testing investigated the genes most widely associated in literature with FEVR: FZD4, LRP5, TSPAN12, and NDP . Clinical and genetic evaluations were extended to relatives of probands positive to genetic testing. Six out of eight probands (75%) showed a genetic variation probably related to the phenotype. We identified four novel genetic variants, one variant already described in association with Norrie disease and one previously described linked to autosomal dominant FEVR. Pedigree analysis of patients led to the classification of four autosomal dominant cases of FEVR (caused by FZD4 and TSPAN12 variants) and two X-linked FEVR probands ( NDP variants). None of the patients showed variants in the LRP5 gene. This study represents the largest cohort study in Italian FEVR patients. Our findings are in agreement with the previous literature confirming that FEVR is a clinically and genetically heterogeneous retinal disorder, even when it manifests in the same family.